2019
DOI: 10.29333/iji.2019.12428a
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Technology Leadership and its Effect on Teachers’ Technology Integration in 21st Century Classrooms

Abstract: This study aims to identify the effect of Principals' Technology Leadership on Teachers' Technology Integration in Malaysian secondary schools. This is a crosssectional survey where systematic random sampling was carried out to select 47 principals and 375 teachers from National Secondary Schools in the northern region of Kedah, Malaysia. Two questionnaires were used: Principals Technology Leadership Assessment (PTLA), which is based on the International Society for Technology in Education (ISTE)-Standards for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 19 publications
(18 reference statements)
1
35
1
6
Order By: Relevance
“…The success of ISTE in establishing the characteristics of technology leadership deserves the highest recognition of any educational organization that practices it. Notably, in most studies, the NETS-A has shown that there are positive signs in building the character of prominent educational leaders [18][19] [20]. Although there are differences in items in the PTLA, in most studies, they still use the original NETS-A instrument as their primary reference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of ISTE in establishing the characteristics of technology leadership deserves the highest recognition of any educational organization that practices it. Notably, in most studies, the NETS-A has shown that there are positive signs in building the character of prominent educational leaders [18][19] [20]. Although there are differences in items in the PTLA, in most studies, they still use the original NETS-A instrument as their primary reference.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are differences in items in the PTLA, in most studies, they still use the original NETS-A instrument as their primary reference. For example, the study of [18] proves that all dimensions of PTLA are high. This is supported by [19], who acknowledged that technology leadership levels would be high if all principals are able to increase ICT competencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those in charge of educational institutions can help support digital citizenship through their leadership skills. Thannimalai and Raman (2018) found an important link between the leadership demonstrated in IT skills by school principals and administrators and the amount of technology employed by teachers. It is therefore apparent that educational programmes must highlight leadership based on technology in order to improve the integration of that technology in classrooms (López & Bernal 2016).…”
Section: Digital Citizenship and Teachingmentioning
confidence: 99%
“…Technology leadership that provides educational technology being used effectively plays a vital role on school goals (Anderson & Dexter, 2005;Papa, 2011;Schiller, 2003). In recent years technology leadership in education has been a topic for extensive researches in a global context (Alenezi, 2017;Apsorn et al, 2019;Chang, 2019;Esplin et al, 2018;Gallego-Arrufat et al, 2017;Gonzales, 2019;Moreira et al, 2019;Raman et al, 2019;Thannimalai & Raman, 2018). In order to reveal what the studies conducted present exactly, two studies that can also be called as the current literature's tomography are like a road map for researchers within the context of technology leadership (Dexter, Richardson & Nash et al, 2016;Dexter & Richardson, 2020).…”
Section: Technology Leadershipmentioning
confidence: 99%